Assessing the acceptability, feasibility, and usefulness of a psychosocial screening tool to patients and clinicians in a clinical genetics service in Australia. Issue 3 (17th November 2021) - Monohan, Katrina; Purvis, Rebecca; Sexton, Adrienne; Kentwell, Maira; Thet, Monica; Stafford, Lesley; Forrest, Laura
Abstract: Increasing demand for clinical genetic services may impact the resources and quality of genetic counseling, potentially impacting patient outcomes. Using a psychosocial screening tool may aid the provision of genetic counseling by reliably identifying patients' psychosocial needs. The Genetic Psychosocial Risk Instrument (GPRI) is a validated genetic‐specific screening tool designed to identify psychological risk factors that predict distress in patients having genetic testing. This questionnaire‐based study investigated the perceived acceptability, feasibility, and usefulness of the GPRI in patients and clinicians in routine clinical genetic practice. From December 2018 to January 2019, 154 patients attending an Australian clinical genetic service were invited to complete a paper‐based survey that included the GPRI. The GPRI was scored and provided to the clinician for use in the appointment. In February 2019, clinicians completed an anonymous online survey regarding acceptability, feasibility, and usefulness of the GPRI. Descriptive statistics, chi‐squared, t tests, and regression analyses were used to analyze the patient data, and descriptive statistics were employed for clinician surveys. A total of 145 patients participated (94% response rate). The average GPRI score was 46.3 (95% CI 43.6—49.0) with 41% of patients meeting the 50‐point threshold indicating high risk for psychological distress. The GPRI was highly acceptable to patients, regardless of their level of psychosocial risk. Fourteen clinicians participated (54% response rate): 85% found the GPRI not too time consuming, and 86% believed it improved patient care by identifying patient needs. All were willing to use the GPRI routinely. The use of the GPRI is highly acceptable to patients and clinicians in this setting, assisting in identifying patients at risk for distress, prompting clinicians to address concerns, provide psychosocial support, and consider ongoing referral. As 41% of patients' scores indicated a high risk of distress, the GPRI is an important tool for potentially enhancing overall patient outcomes.